Les constructions agricoles contemporaines : des objets discrets de la modernisation agricole - Philippe Madeline (In Situ)
Agricultural modernization in the second half of the 20th Century radically changed the hardware environment of farms. Whether one approaches the specialization of production, mechanization or automation activities, advances in productivity or improved working conditions, geographers have met all these changes. Among them, they preferred aspects such as structural transformations parcel or equipment tractors when other manifestations of the establishment of a “model”productivist agriculture remained much more discreet. The farm buildings are a good example.